Effects of acid-pak 4-wayTM, virginiamycin and early age feed restriction on broiler chickens exposed to high ambient temperature - Juriah Kamaludeen.
This study was conducted to compare the effects of Acid-Pak 4-WayTM, virginiamycin and early age feed restriction on performance and physiology of chickens exposed to high ambient temperature. Chicks were brooded for three weeks and then maintained at 24 +/- 1 degree C. On day (d) 0, chicks were assigned to one of four feeding regimens: (1) ad libitum provision of basal diet and untreated drinking water (control); (2) ad libitum provision of basal diet + 40g/100kg virginiamycin and untreated drinking water (VM); (3) ad libitum provision of basal diet and drinking water containing 0.5g/L (d 1 to 7, d 11, 20 and 22) or 1.0g/L (d35, d 36 to 42) Acid Pak 4-WayTM (AP) or (4) 60% feed restriction of basal diet on d 4, 5 and 6 and untreated drinking water (F60). From d 35 to 42, all chicks were exposed to 34+/-1 degree C for 6 h/d. Following 7 days of heat challenge the VM, AP and F60 birds had better body weight and feed conversions ratios than controls. The AP chicks were less hyperthermic than controls in responce to the heat treatment. The body temperature of VM and F60 birds were not significant different from their AP and control counterparts. One day of heat treatment resulted in hyperglycemia in the controls but not those of VM, AP and F60 chicks. Supplementing birds with AP elevated serum concentration of sodium as compared to other birds. While the serum concentration of potassium of AP birds was higher than controls, it was not significantly different from those of VM and F60. The VM, AP and F60 chicks had smaller increases in heterophil to lymphocyte ratios than those of controls throughout the duration of heat exposure. Mortality during heat treatment was not significantly affected by feeding regimens. It is concluded that although the VM, AP and F60 regimen are beneficial for alleviating, the detrimental effects of heat stress in male broiler chickens, the F60 procedure is more realistic is more realistic and practical as it does not incur on production costs.